Correlation Between Soluble Klotho and Vascular Calcification in Chronic Kidney Disease: A Meta-Analysis and Systematic Review - Liu, QiFeng; Yu, LiXia; Yin, XiaoYa; Ye, JianMing; Li, ShaSha (Frontiers in Physiology, 2021)
Background: The correlation between soluble Klotho (sKlotho) level and vascular calcification (VC) in patients with chronic kidney disease (CKD) remains controversial. We aimed to address this controversy and assess the feasibility of applying sKlotho as a biomarker for VC by using meta-analysis. Methods: Medical electronic databases were thoroughly searched for eligible publications on the association between sKlotho level and VC in CKD patients. Effectors, including correlation coefficients (r), odds ratios (ORs), hazard ratio (HR) or β-values, and 95% confidence intervals (CIs) were extracted and combined according to study design or effector calculation method. Pooled effectors were generated using both random-effects models and fixed-effects models according to I2 value. Origin of heterogeneity was explored by sensitivity analysis and subgroup analysis. Results: Ten studies with 1,204 participants from a total of 1,199 publications were eligible and included in this meta-analysis. The combined correlation coefficient (r) was [-0.33 (-0.62, -0.04)] with significant heterogeneity (I2 = 89%, p < 0.001) based on Spearman correlation analysis, and this significant association was also demonstrated in subgroups. There was no evidence of publication bias. The combined OR was [3.27 (1.70, 6.30)] with no evidence of heterogeneity (I2 = 0%, p = 0.48) when sKlotho was treated as a categorical variable or [1.05 (1.01, 1.09)] with moderate heterogeneity (I2 = 63%, p = 0.10) when sKlotho was treated as a continuous variable based on multivariate logistic regression. No significant association was observed and the pooled OR was [0.29 (0.01, 11.15)] with high heterogeneity (I2 = 96%, p < 0.001) according to multivariate linear regression analysis. There was an inverse association between sKlotho and parathyroid hormone levels. The combined coefficient (r) was [-0.20 (-0.40, -0.01)] with significant heterogeneity (I2 = 86%, p < 0.001), and without obvious publication bias. No significant association was found between sKlotho and calcium or phosphate levels. Conclusion: There exists a significant association between decreased sKlotho level and increased risk of VC in CKD patients. This raises the possibility of applying sKlotho as a biomarker for VC in CKD populations. Large, prospective, well-designed studies or interventional clinical trials are required to validate our findings.